Humanité et dépassement dans l’œuvre de Ferran Delèris (1922-2009) - Joëlle Ginestet (Lengas)
Ferran Delèris (Ferdinand Déléris) born in Rouergue countryside in the twenties, lived in Vietnam and Madagascar. Besides essays and novels in French, he wrote narrative fictions, memoirs and a book of poems in Occitan. To this heir to war accounts heard in his family –1870 and mainly 1914-1918 –, to this member of the Resistance movement during the second world war and to this witness of the conflicts that would lead to the French colonies independence, going back to his mother tongue seems to have stimulated him in his attempt to understand why a man agrees to fight. The Occitan language he studied and explored, may have given Ferran Delèris, a man of action, the ability to freely fulfil himself as a writer.